Photoynthetic and productive increase in tomato plants treated with strobilurins and carboxamides for the control of Alternaria solani - Marek, Janaina; de Azevedo, Dione; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP]; Faria, Cacilda Marcia Duarte Rios (Elsevier, 2018)
During two years (2015 and 2016), an experiment was carried out to investigate the effects of the application of strobilurin and carboxamides on the photosynthetic efficiency and yield of tomato plants inoculated with A. solani grown in greenhouse in southern Brazil. The experimental design was randomized blocks with five replicates and seven treatments: inoculated control (water + inoculum), absolute control (water), boscalid (0.075 g L−1), boscalid (0.100 g L−1) + kresoxim-methyl (0.050 g L−1), pyraclostrobin (0.100 g L−1), fluxapyroxad (0.058 g L−1) + pyraclostrobin (0.116 g L−1) and methyl (1.100 g L−1) + pyraclostrobin (0.100 g L−1), applied at 15 days after transplantation, at intervals of 15 days, totaling 6 applications. The effect on plant development was evaluated by plant height, leaf area, fresh and dry mass of leaves, stem and roots. To verify the photosynthetic efficiency, gas exchange, chlorophyll a fluorescence, content of photosynthetic pigments, nitrate reductase enzyme activity, carbohydrate content and yield were evaluated. All fungicides positively affected the evaluated parameters, improving photosynthetic efficiency and fruit production, in addition to providing efficient disease control. However, treatments using fluxapyroxad with pyraclostrobin, followed by metiram with pyraclostrobin stood out for promoting high photochemical yield due to the higher levels of photosynthetic pigments, activity of the nitrate reductase enzyme and, consequently, increase in the synthesis and translocation of photoassimilates. These results demonstrate the benefits of the use of these agrochemicals in the control of A. solani in tomato.
Keywords: Fungicides; Photosynthesis; Physiological effect; Solanum lycopersicum